Isolation of Endophytic Colletotrichum gloeosporioides Penz. from Salacia chinensis and its Antifungal Sensitivity - Sharma, K. R. Chandrashekar*, N. Bhagya, Sana Sheik, M. Samhitha (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Salacia chinensis<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> L (Celestraceae), an endangered medicinal plant is well known for its antidiabetic activity. An attempt of in Ã¢â‚¬â€œ vitro culturing to micropropagate the plant led to the discovery of an endophytic association of Colletotrichum gloeosporioides Penz. with both stem and leaf of the plants. The fungus did not respond to the lower concentrations of Amphotericin B and Nystatin (upto 60 Ã‚Âµg/ml) in the culture medium. However, it was sensitive at a higher concentration of 100Ã‚Âµg/ml.